Strengthening Leadership Culture (The Role of Kyai in Indonesian Pesantren) - Naufal Ahmad Rijalul Alam (At-Ta'dib, 2018)
Pesantren is the traditional Islamic education system and the oldest non-formal institution in Indonesia. In order to its role, this boarding school has many contributions in the strengthening of education culture, specifically in building and concerning the identity of Islam. Some scholar proved the important role of Pesantren in transferring Islamic knowledge, strengthening people’s religious loyalty to Islamic principles. In addition, Pesantren has two roles: teaches religion knowledge and encourage it’s student or santri to develop globally. All of thus cannot be separated from the Kyai role as an owner and a leader to manage its community. As an official subject, leadership practice of Kyai seems to be high expected to inculcate education. Kyai in Pesantren plays many roles such as educator and caregiver, society connector, leader, and manager of the Pesantren. This paper aims to find the role of Kyai in Pesantren as the leader in managing an educational system inside it. By using the literature research, the writer found that Kyai's leadership as a symbol and strength in building values. Santri character, actually not only dealing with the process of education, but also for every santri have a duty as a successor and educator in the future, the spreader mission Islamic da’wa that eventually became the guard and fortress of the ummah. The sustainability and its existence of Pesantren are on Kyai as the leader, main holder, policymaker, especially in the sphere of education and educating society.